483 Improvement in Behavioral, Cellular and Molecular Outcomes with Connexin Inhibitors Administration in a Porcine Spinal Cord Injury Model. (1st April 2022) - Alok, Khaled; Moussalem, Charbel; Minassian, Georges; Baassiri, Wassim; Kobeissy, Firas; Jurjus, Abdo; Hamade, Eva; Ayoub, Abeer J.; Habib, Aida; Fahs, Assil; El Houshiemy, Mohamad N.; Bsat, Shadi; et al.
Abstract : INTRODUCTION: Connexin inhibition has demonstrated promising results in rodents spinal cord injury models (SCI) as a neuroprotective strategy that improves SCI outcomes. However, it has not been tested in a larger animal yet, a necessary step before conducting a human clinical trial. METHODS: SCI was induced using a compression/contusion weight drop model in three groups of pigs with 2 animals per group. Group A: control, Group B: treated with nonselective gap junctions blocker: Carbenoxolone, Group C: treated with connexin-43 memetic peptide: Gap26. All medications were delivered intrathecally at the time of injury. We assessed the locomotor development of the animals over 11 weeks. After which the animals were euthanized and their spinal cords were harvested for histological and immunofluorescence assessment. RESULTS: Treatment with intrathecal connexins inhibitors improved SCI outcomes. In terms of locomotion recovery, Groups B and C regained the stepping ability in their hind limbs, whereas the control group did not. Similarly, groups B and C exhibited a decreased level of astrocytes activation at the injury site, and their PGE2 serum levels remained low in the two treated groups. The histological damage was particularly limited in Gap 26-treated group (C). CONCLUSION: We translated the positive neuroprotective effect of a connexin-43 mimetic peptide and a gap junction blocker in a porcine SCI model. This study supports the potential role of these agents in improving SCI outcome.